Grass carp (Ctenopharyngodon idella) SIRT7 negatively regulates HIF-1 signaling pathway by interacting with HIF-1α independent of deacetylase activity under hypoxia - Shuo Zhang; Yuanxin Yang; Yuting Song; Songlin Chen; Guobin Hu (Aquaculture, 2027)

Isolation and structural elucidation of immunomodulatory oligosaccharides from Trillium tschonoskii - Juan Song; Si Liu; Meng Sun; Guangzhong Tu; Zhiqiang Zhang; Yue Liu; Yi Nan; Guobin Shen; Xiaojuan Chen; Haizhen Liang; Bin Liu; Baiping Ma (Glycoconjugate Journal, 2026)

Insights into the role of TLR21 in innate immunity of Japanese flounder (Paralichthys olivaceus) - Yuting Song; Yuanxin Yang; Shuo Zhang; Songlin Chen; Guobin Hu (Fish & Shellfish Immunology, 2026)

Mask Auto-Labeler: A unified framework for semi-automatic annotation and segmentation in mineral processing - Kanghui Zhang; Qingkai Wang; Guobin Zou; Jiawei Yang; Tao Song; Meng Liu; Haiyang Zhang; Yuhan Fan (Minerals Engineering, 2026)

Sediment-mediated coupling of hyporheic exchange and land use drives macroinvertebrate community structure - Mengdan Guan; Wei Hong; Nan Li; Jinxi Song; Guobin Fu; Shilei Yang; Haoying Zhang; Mengyang Yang; Haozheng Sun (Journal of Cleaner Production, 2026)

Hypertension-dependent effects of SGLT2 inhibitors on coagulation parameters in patients with coronary artery disease: a retrospective cohort study - Xiaoyue Qin; Guobin Song; Yunqi Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Design and optimisation of differentiated UAV-based fertiliser applicator - Jingang Han; Guobin Wang; Xinyu Xue; Cancan Song; Yubin Lan (Biosystems Engineering, 2026)

Characterization of TLR14 ligands, adaptor proteins and immune mechanisms in Japanese flounder (Paralichthys olivaceus) - Yuting Song; Zhihong Gong; Songlin Chen; Guobin Hu (Fish & Shellfish Immunology, 2025)

Pollution characteristics, ecological risk and microbial response to combined heavy metals and polycyclic aromatic hydrocarbons in soil-groundwater system of the blown-sand region - Xiaobang Liu; Lei Duan; Yaqiao Sun; Chenchen Xie; Guobin Song (Environmental Research, 2025)

Environmental Stresses Constrain Soil Microbial Community Functions by Regulating Deterministic Assembly and Niche Width - Xiaojun Wang; Jie Wang; Ji Chen; T. Martijn Bezemer; Zilin Song; Wolfgang Wanek; Guobin Liu; Chao Zhang (Molecular Ecology, 2025)
Increasing evidence indicates that the loss of soil microbial α‐diversity triggered by environmental stress negatively impacts microbial functions; however, the effects of microbial α‐diversity on community functions under environmental stress are poorly understood. Here, we investigated the changes in bacterial and fungal α‐ diversity along gradients of five natural stressors (temperature, precipitation, plant diversity, soil organic C and pH) across 45 grasslands in China and evaluated their connection with microbial functional traits. By quantifying the five environmental stresses into an integrated stress index, we found that the bacterial and fungal α‐diversity declined under high environmental stress across three soil layers (0–20 cm, 20–40 cm and 40–60 cm). Metagenomic‐based analyses showed that the diversity of functional genes decreased along the stress gradients. High stress enhanced the abundance of genes associated with broad functional categories (e.g., glycolysis/gluconeogenesis, TCA cycle, DNA replication/repair and cell growth/death) but reduced the abundance of genes linked to specialised functional categories (e.g., C, N, S and methane metabolism). Phylogenetic null models and niche analyses indicated that stochastic assembly processes predominated in high‐diversity communities, in which bacterial and fungal taxa had a narrow ecological niche. However, in low‐diversity communities, deterministic assembly processes were dominant, and taxa had wide niches, correlating with the reduction in gene abundance observed for broad and specialised functional categories. Given the essential role of the microbiome in regulating ecosystem functions, our findings suggest that low‐diversity‐induced deterministic community assembly processes and a wide niche under high environmental stress may regulate microbial functions. These findings emphasise the ecological mechanisms through which microbial biodiversity regulates terrestrial ecosystem functioning.

Shifts in Genome Size and Energy Utilization Strategies Sustain Microbial Functions Along an Aridity Gradient - Xiaojun Wang; Wancai Wang; Lei Deng; Ting Li; Shilong Lei; Lu Zhang; Lirong Liao; Zilin Song; Guobin Liu; Chao Zhang (Global Change Biology, 2025)
Microbes acquire energy to sustain their survival and function through the decomposition of organic carbon (C) or by oxidizing atmospheric trace gases (e.g., H 2 , CO, CH 4 ). However, how these two microbial energy‐acquisition strategies change along environmental gradients and the underlying mechanisms are unclear. This study investigated the energy strategies and genomic traits of soil microbiomes along a natural aridity gradient, ranging from semi‐humid forests to arid deserts. By analyzing 374 metagenome‐assembled genomes from 13 microbial phyla, we found that the most prevalent microbes are metabolically versatile aerobes that use atmospheric trace gases to support aerobic respiration, C fixation, and N, P, and S cycling. Soil microbes adapt genomic traits associated with reduced energy expenditure in more arid soils, including smaller genome sizes, lower GC content, and fewer 16S rRNA gene copies. Microbial communities in diverse arid habitats are capable of utilizing organic compounds and the oxidation of trace gases (e.g., H 2 , CO, CH 4 , and H 2 S) as energy sources. However, the utilization of organic energy decreased while reliance on trace gas oxidation increased with increasing aridity. Higher consumption rates of H 2 , CO, and CH 4 in desert soils from ex situ culture experiments confirmed that increased aridity stimulates microbial oxidation of atmospheric trace gases. This shift in energy utilization was strongly correlated with declining soil organic C levels. As organic C decreased along the aridity gradient, the abundance of trace gas oxidizers (both specialized and multi‐gas oxidizers) increased significantly, while that of non‐oxidizers declined. Trace gas oxidizers exhibited smaller genomes, lower 16S rRNA operon copy numbers, and slower predicted growth rates, indicative of oligotrophic lifestyles. In contrast, copiotrophic non‐oxidizers had larger genomes and faster growth rates. These findings reveal that microbial communities adapt their genomic traits and energy‐acquisition strategies to sustain functionality across aridity gradients, enhancing our understanding of soil microbiome responses to climate change.

Effects of different spray parameters of plant protection UAV on the deposition characteristics of droplets in apple trees - Changfeng Shan; Chen Xue; Lechun Zhang; Cancan Song; Rehana Kaousar; Guobin Wang; Yubin Lan (Crop Protection, 2024)

Numerical and experimental investigation on the whirling vibration characteristic of ship propulsion shafting under multi-source uncertainty - Lixun Lu; Guobin Li; Pengfei Xing; Honglin Gao; Yuchao Song; Hongpeng Zhang (Ocean Engineering, 2024)

Hexafluoropropylene oxide trimer acid (HFPO-TA) disrupts sex differentiation of zebrafish (Danio rerio) via an epigenetic mechanism of DNA methylation - Dan Yang; Fanghua Li; Xiaohui Zhao; Shasha Dong; Guobin Song; Haonan Wang; Xiaoying Li; Guanghui Ding (Aquatic Toxicology, 2024)

Controlling CO2 hydrogenation selectivity by tuning surface properties of Cu/Zn Al O catalysts - Lixin Song; Guobin Liu; Zhenping Qu (Chemical Engineering Journal, 2024)

Prediction of cotton FPAR and construction of defoliation spraying prescription map based on multi-source UAV images - Lechun Zhang; Binshu Sun; Denan Zhao; Changfeng Shan; Guobin Wang; Cancan Song; Pengchao Chen; Yubin Lan (Computers and Electronics in Agriculture, 2024)

Aridity thresholds of microbiome-soil function relationship along a climatic aridity gradient in alpine ecosystem - Lu Zhang; Lirong Liao; Feike A. Dijkstra; Xiangtao Wang; Manuel Delgado-Baquerizo; Guobin Liu; Guoliang Wang; Zilin Song; Jie Gu; Chao Zhang (Soil Biology and Biochemistry, 2024)

Fuzzy Logic-Based Decision-Making Method for Ultra-Large Ship Berthing Using Pilotage Data - Yibo Li; Guobin Song; Tsz-Leung Yip; Gi-Tae Yeo (Journal of Marine Science and Engineering, 2024)
As seafarers are involved in Maritime Autonomous Surface Ships (MASS), except for those in the fourth level of autonomy, the decision making of autonomous berthing should be carried out and be understood by human beings. This paper proposes a fuzzy logic-based human-like decision-making method for ultra-large ship berthing, which considers locations, ship particulars and the natural environment, and these factors are treated as the input variables. The IF–THEN rules are then established after the fuzzification of the input variables and are used for fuzzy inference to derive the decision of ship handling. It can be implemented in the decision-making system for safe navigation or be included in the process of autonomous berthing. The pilotage data are collected with nautical instruments and a distance measurement system during the berthing process, which are used to validate the proposed model and calculate the speed and turn errors. The overall and individual error of the decision-making model is in a reasonable and small range, which indicates that the model has good accuracy. The results of this research offer theoretical and practical insights into the development of a human-like decision-making method for autonomous navigation in port waters and maritime safety management in the shipping industry. The model can be further applied to develop a more widely applicable decision-making system for autonomous navigation in confined waters.

Simplified microbial network reduced microbial structure stability and soil functionality in alpine grassland along a natural aridity gradient - Chao Zhang; Shilong Lei; Hongyue Wu; Lirong Liao; Xiangtao Wang; Lu Zhang; Guobin Liu; Guoliang Wang; Linchuan Fang; Zilin Song (Soil Biology and Biochemistry, 2024)

Urea fertilization increased CO2 and CH4 emissions by enhancing C-cycling genes in semi-arid grasslands - Xiaojun Wang; Jie Wang; Yanuo Zou; Yujing Bie; Athar Mahmood; Lu Zhang; Lirong Liao; Zilin Song; Guobin Liu; Chao Zhang (Journal of Environmental Management, 2024)

Numerical calculation and experimental investigation of the dynamic alignment of ship propulsion shafting based on Latin hypercube stochastic finite element - Lixun Lu; Guobin Li; Pengfei Xing; Honglin Gao; Yuchao Song; Hongpeng Zhang (Ocean Engineering, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Transcriptome analysis reveals immune-related genes in tissues of Vibrio anguillarum-infected turbot Scophthalmus maximus - Yuting Song; Maqsood Ahmed Soomro; Xianzhi Dong; Guobin Hu (Journal of Oceanology and Limnology, 2024)

Efficient removal of organic pollutants by activation of peroxydisulfate with the magnetic CoFe2O4/carbon nanotube composite - Yawei Shi; Yi Zhang; Guobin Song; Ya Sun; Guanghui Ding (Environmental Science and Pollution Research, 2023)

A review of stochastic finite element and nonparametric modelling for ship propulsion shaft dynamic alignment - Lixun Lu; Guobin Li; Pengfei Xing; Honglin Gao; Yuchao Song (Ocean Engineering, 2023)

Mapping the landscape of ship berthing research: A bibliometric analysis and literature review over two decades - Diao Han; Houzhong Chen; Guobin Song; Tsz Leung Yip; Bing Wu (Ocean & Coastal Management, 2023)

Facile Fabrication of Amino Functionalized Magnetic Multi-walled Carbon Nanotubes for Removal of Congo Red from Aqueous Solutions - Guobin Song; Liya Tong; Shuhua Chen; Jing Zhang; Yi Zhang; Haonan Wang; Yawei Shi; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2022)

A Multi-Method Approach to Identify the Natural Frequency of Ship Propulsion Shafting under the Running Condition - Pengfei Xing; Lixun Lu; Guobin Li; Xin Wang; Honglin Gao; Yuchao Song; Hongpeng Zhang (Journal of Marine Science and Engineering, 2022)
In order to identify the natural frequency of ship propulsion shafting under the running condition, a multi-method approach that combines Duffing Oscillator, harmonic wavelet packet transform, and probability density function is proposed. An experimental investigation on the natural frequency of running propulsion shafting is conducted on the ship propulsion shafting test bench, and the natural frequency response of running propulsion shafting under different alignment states is obtained from the measured bearing vibration signal. The results show that the natural frequency of propulsion shafting can be excited under the running condition, but its response is feeble. When the alignment state of the propulsion shafting gradually changes with the elevation of the front stern bearing, the identified natural frequency of the propulsion shafting shows an upward trend. In contrast, its amplitude shows a downward trend. Therefore, the proposed approach can identify the natural frequency of the ship propulsion shafting from the measured bearing vibration signal under the running condition.

Transcriptome analysis of turbot ( Scophthalmus maximus ) head kidney and liver reveals immune mechanism in response to Vibrio anguillarum infection - Yuting Song; Xianzhi Dong; Guobin Hu (Journal of Fish Diseases, 2022)
The diseases triggered by Vibrio anguillarum infection have created huge economic losses to the turbot ( Scophthalmus maximus ) farming industry. However, the immune mechanism of turbot to V. anguillarum infection has not been deeply investigated. To better understand the immune response of turbot to V. anguillarum infection, transcriptome analysis of the head kidney and liver of turbot was performed. A total of 15,948 and 11,494 differentially expressed genes (DEGs) were obtained from the turbot head kidney and liver, respectively. Transcriptome analysis revealed that the head kidney and liver of turbot have some differences in the gene ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis of the DEGs for the different functions of these two organs. Although there are many uncertain factors in this immune process, such as the occurrence of alternative splicing (AS) events and the differences in the protein structure of the DEGs, the NFκB signalling pathway, MKK‐dependent AP‐1 activation, JAK‐STAT signalling pathway, the signal transmission of MHC Ⅰ and a series of DEGs including HSP90 driving NLRP3 to produce inflammatory factors (IL‐1β, IL‐8, TNFα, etc.) were possible important immune response pathways for turbot to V. anguillarum infection. Overall, our research has conducted a preliminary exploration of the immune mechanism of turbot in response to V. anguillarum infection.

Magnetic graphene oxide for methylene blue removal: adsorption performance and comparison of regeneration methods - Yawei Shi; Haonan Wang; Guobin Song; Yi Zhang; Liya Tong; Ya Sun; Guanghui Ding (Environmental Science and Pollution Research, 2022)

Mdivi-1 Modulates Macrophage/Microglial Polarization in Mice with EAE via the Inhibition of the TLR2/4-GSK3β-NF-κB Inflammatory Signaling Axis - Xiaoqin Liu; Xiaojuan Zhang; Xiaojie Niu; Peijun Zhang; Qing Wang; Xiuhua Xue; Guobin Song; Jiezhong Yu; Guoping Xi; Lijuan Song; Yanhua Li; Cungen Ma (Molecular Neurobiology, 2022)

Sorptive removal of methylene blue from water by magnetic multi-walled carbon nanotube composites - Guobin Song; Anqi Li; Yawei Shi; Wanran Li; Haonan Wang; Chunchao Wang; Ruijuan Li; Guanghui Ding (Environmental Science and Pollution Research, 2021)

Impact of soil leachate on microbial biomass and diversity affected by plant diversity - Chao Zhang; Jie Wang; Guobin Liu; Zilin Song; Linchuan Fang (Plant and Soil, 2019)

Response of rhizosphere microbial communities to plant succession along a grassland chronosequence in a semiarid area - Zilin Song; Guobin Liu; Chao Zhang (Journal of Soils and Sediments, 2019)

Urea fertilization decreases soil bacterial diversity, but improves microbial biomass, respiration, and N-cycling potential in a semiarid grassland - Chao Zhang; Zilin Song; Daohua Zhuang; Jie Wang; Sisi Xie; Guobin Liu (Biology and Fertility of Soils, 2019)

Spatial–temporal variations of spring drought based on spring-composite index values for the Songnen Plain, Northeast China - Xiaoyan Song; Lijuan Li; Guobin Fu; Jiuyi Li; Aijing Zhang; Wenbin Liu; Kai Zhang (Theoretical and Applied Climatology, 2014)

The distribution and ultrastructure of the forming blood capillaries and the effect of apoptosis on vascularization in mouse embryonic molar mesenchyme - Guohua Yuan; Li Zhang; Guobin Yang; Jingwen Yang; Chunyan Wan; Lu Zhang; Guangtai Song; Shuo Chen; Zhi Chen (Cell and Tissue Research, 2014)

Projection of future rainfall for the North China Plain using two statistical downscaling models and its hydrological implications - Wenbin Liu; Guobin Fu; Changming Liu; Xiaoyan Song; Rulin Ouyang (Stochastic Environmental Research and Risk Assessment, 2013)

Immunohistochemical localization of the NH2-terminal and COOH-terminal fragments of dentin sialoprotein in mouse teeth - Guohua Yuan; Guobin Yang; Guangtai Song; Zhi Chen; Shuo Chen (Cell and Tissue Research, 2012)

Genetic Structure and Differentiation of Three Chinese Indigenous Cattle Populations - Yongjiang Mao; Hong Chang; Zhangping Yang; Liu Zhang; Ming Xu; Wei Sun; Guobin Chang; Guangming Song (Biochemical Genetics, 2007)